2020
DOI: 10.3389/fpsyg.2020.614887
|View full text |Cite
|
Sign up to set email alerts
|

Re-examining the Role of Coping Strategies in the Associations Between Infertility-Related Stress Dimensions and State-Anxiety: Implications for Clinical Interventions With Infertile Couples

Abstract: Research has shown a direct relationship between infertility-related stress and anxiety in infertile patients. The present study goes into this relationship in depth, testing the moderating role of coping strategies (Seeking Social Support, Avoidant, Positive Attitude, Problem-Solving, Turning to Religion) in the associations between specific infertility-related stress dimensions (Social Concern, Need for Parenthood, Rejection of Childfree Lifestyle, Couple’s Relationship Concern) and State-Anxiety among male … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 62 publications
2
25
1
Order By: Relevance
“…Following this approach, among the wide range of individual characteristics featuring stress processes [ 27 ], coping strategies play an essential role in influencing an individual’s adjustment to situations and, thus, in determining the development of stress-related health outcomes [ 28 , 29 , 30 ]. In line with this, while most research conducted during the COVID-19 pandemic has paid great attention to the sources of stress characterizing university students ‘experiences [ 22 , 23 , 24 , 25 ], some studies have also explored the strategies they have adopted to deal with the new-unprecedented-reality [ 21 , 31 , 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following this approach, among the wide range of individual characteristics featuring stress processes [ 27 ], coping strategies play an essential role in influencing an individual’s adjustment to situations and, thus, in determining the development of stress-related health outcomes [ 28 , 29 , 30 ]. In line with this, while most research conducted during the COVID-19 pandemic has paid great attention to the sources of stress characterizing university students ‘experiences [ 22 , 23 , 24 , 25 ], some studies have also explored the strategies they have adopted to deal with the new-unprecedented-reality [ 21 , 31 , 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, considering the still open debate on stress process and adaptive/maladaptive coping strategies in the literature beyond the COVID-19 emergency [ 27 , 30 ], as well as taking into account the limited evidence on the effectiveness of coping strategies among university students during the pandemic, further research providing evidence-based and updated contributions is needed to promote students’ adjustment in the current period, namely in the crucial aftermath of the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Research shows that people are prone to experience positive changes in the psychological sphere if they can give meaning to a difficult experience (Neimeyer, Baldwin, & Gillies, 2006). It turns out that even in the situation of significantly higher results on the depressiveness scale in women, the use of a positive reframing of the experienced problem by both women and their husbands is so effective that it reduces the impact of depressiveness, leads to stress reduction and greater life satisfaction in., 2021, Zurlo, Della Volta &Vallone, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The selection of strategies for coping with the problem of infertility, in addition to gender, turns out to be related to the level of perceived stress and the perception of infertility as a loss or as a challenge. Women struggling with the problem of infertility experience high anxiety, uncertainty and lack of control (Dana, Narimani, Mikaeili, 2013;Yazdani, Kazemi, Fooladi, & Samani, 2016), which is associated with more frequent use of avoidance strategies, self-blame, denial and distraction (Gourounti et al, 2012, Iordăchescu et al, 2021, Zurlo, Della Volta, Vallone, 2020 and perceiving the problem of infertility as a loss (Kalus, 2014). Also, infertile men with higher levels of stress most often adopted blame and avoidance strategies (Babore, Stuppia, Trumello, Candelori, Antonucci, 2017, Nagórska, Obrzut, Ulman & Darmochwał-Kolarz, 2021.…”
Section: Coping Strategies With Infertility or Miscarriagementioning
confidence: 99%
“…Research ndings based on infertile men found that anxiety may be associated with decreased semen quality [22][23][24] . A controlled study of 94 patients undergoing in vitro fertilization (IVF) and 85 normal subjects showed that increased levels of state and trait anxiety were associated with decreased semen volume, sperm concentration, total sperm count, and decreased sperm motility [14] .…”
Section: Introductionmentioning
confidence: 99%